2014
DOI: 10.1590/1414-462x201400010007
|View full text |Cite
|
Sign up to set email alerts
|

Use of dental services in areas covered by the Family Health Strategy in Olinda, Brazil

Abstract: Objective: The aim of the present study was to analyze factors associated with the use of dental services in areas covered by the Family Health Strategy in the city of Olinda, northeastern Brazil. Methods: A quantitative, analytical, cross-sectional study was conducted involving individuals over 18 years of age (n=492) registered at Family Health Units. Data analysis was performed with SPSS program (version 11.0) and involved 2 test and logistic regression analysis. Results: The number of individuals who sough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
2
2
0
6
Order By: Relevance
“…Besides the known physical and functional limitations, the results of the present study also suggest that oral problems have psychological repercussions reflected in attitudes such as difficulty to relax, embarrassment, stress, and preoccupation with one's oral situation, all of which can interfere in the field of social relationships. Other investigations have also shown that the greater the progression of the disease and its oral involvement, the greater the repercussion in the psychological domain . Again, in the present study the highest means of OHIP‐14 extent and severity were observed in the group with the worst oral conditions (individuals with combined caries and periodontitis).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Besides the known physical and functional limitations, the results of the present study also suggest that oral problems have psychological repercussions reflected in attitudes such as difficulty to relax, embarrassment, stress, and preoccupation with one's oral situation, all of which can interfere in the field of social relationships. Other investigations have also shown that the greater the progression of the disease and its oral involvement, the greater the repercussion in the psychological domain . Again, in the present study the highest means of OHIP‐14 extent and severity were observed in the group with the worst oral conditions (individuals with combined caries and periodontitis).…”
Section: Discussionsupporting
confidence: 62%
“…Other investigations have also shown that the greater the progression of the disease and its oral involvement, the greater the repercussion in the psychological domain. 7,12,38 Again, in the present study the highest means of OHIP-14 extent and severity were observed in the group with the worst oral conditions (individuals with combined caries and periodontitis). In the group with caries or periodontitis alone, only the mean scores of OHIP-14 severity were statistically significant, showing a clear distinction between individuals exposed to caries and periodontitis and those without these oral problems.…”
Section: Discussionsupporting
confidence: 50%
“…(LOURENÇO et al, 2009;MATTOS et al, 2014;RON-CALLI, 2007) Além disso, os estudos contemplam aspectos relacionados ao acesso e/ou utilização dos serviços de saúde bucal em áreas cobertas pela ESF. (SANTOS et al, 2007;CHAVES et al, 2012;SOARES et al, 2013;OLIVEIRA et al, 2014) Os estudos de base populacional (CHAVES et al, 2012;OLIVEIRA et al, 2014;PEREIRA et al, 2009;PEREIRA et al, 2012;ROCHA, GOES, 2008;SOA-RES et al, 2013) têm evidenciado diferentes resultados com relação à inclusão da ESB/ESF nos municípios.…”
Section: Segundo Mandato Dilma Roussef (2015)unclassified
“…Assim, a desigualdade de acesso e no uso de serviços é encontrada mesmo em áreas aparentemente homogêneas [22].…”
Section: Metodologiaunclassified